Pengaruh Pemberian Probiotik Bahan Herbal pada Pakan terhadap Pertumbuhan Benih Ikan Gabus - Ibrahim, Noprian; Parirska, Donny; Lestari, Siti (Penerbit Goodwood, 2024)
Purpose: The purpose of this study was to determine the effect of giving different herbal probiotics to feed on growth in absolute length, absolute weight, SGR, FCR, and SR. be information for snake head fish cultivators on feed efficiency in increasing production. Methods: This study was conducted over 30 days in May. The research used a completely randomized design (CRD) with four treatments and three replications. Results: The results of this study provide basic information to increase productivity in the maintenance of snake head fish seeds in a controlled manner using probiotics at a dose of 10 ml/kg of feed. The best results showed that the use of herbal probiotics at a dose of 10 ml/kg of feed resulted in a survival rate (71.11%), the highest growth rate (3.77%), and the best feed conversion (1.2).Conclusions: The study found that administering 10 ml/kg of herbal probiotics improved cork fish seed growth, achieving a 71.11% survival rate, 3.77% growth rate, and 1.36 feed conversion, providing key insights for enhancing controlled fish seed cultivation productivity. Limitations: Based on the results of the study, the use of probiotics at a dose of 10 ml/kg of feed improved the growth performance of snake head fish seeds reared in controlled containers. Contribution: The snake head fish is a swamp fish that has important economic value because it has many benefits. In the field of medicine, snake head fish are often used to help speed up recovery after surgery.